Analyses of non-native Estonian, Latvian, and Swedish young learners’ written production in EFL: similarities and differences - Sundh, Stellan (Frontiers in Education, 2024)
Assessments of written production in English as a foreign language play an important role in the overall grading of learners' English at school. The other three skills than writing are evidently also considered but written texts are useful to work with since they provide concrete material easily available to study when it comes to learners' levels of achieved language proficiency. The teachers' overall and immediate impression of the text could play a significant role for the final grading of the production. It is therefore worth investigating the variation of linguistic features in texts of similar length produced by learners of the same age.In the present study, young learners' written production in English is analysed with several approaches. The learners' texts were of similar length and language quality but had different characteristics in terms of structure and style. The results show an overall picture of what factors might influence teachers' assessment of young learners' texts in EFL and are therefore useful information to consider for teachers of English to ensure valid and reliable assessments of learners' written productions of English as a foreign language.